Handbook of manufacturing engineering - Walker, Jack M. (Manufacturing engineering and materials processing, 1996)
Provides single-source coverage on the full range of activities that meet the manufacturing engineering process, including management, product and process design, tooling, equipment selection, faciltiy planning and layout, plant contruction, materials handling and storage, method analysis, time standards, and production control. The text examines every topic involved with product and factory development, parts fabrication, and assembly processes.